Citizenship education for Africans in South Africa (1948-1994): A critical discourse (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The paper presents a critical discussion of the provision of citizenship education for Africans in South Africa during the period 1948-1994. Aconceptual analysis of Johnson and Morris’ critical citizenship framework and its four dimensions, namely, ideology, the collective, self and praxis, ispresented. Utilising this framework, the author examines the goals and aims of the former National Party government in their project to provide citizenshipeducation through history, social science and civics teaching in schools for African students. The study suggests that the goal of the state in promotingcitizenship education during the former political dispensation as seen through the four dimensions did not create space for critical thinking and dialogue,crucial elements for critical citizenship education. Recommendations with regard to the form and content of citizenship education in future are made.
Keywords: Citizenship; Citizenship education; Critical citizenship education; Critical thinking; Curriculum